2020
DOI: 10.1002/hbm.25091
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural connectome in relation to PRRT2 mutations in paroxysmal kinesigenic dyskinesia

Abstract: This study explored the topological characteristics of brain white matter structural networks in patients with Paroxysmal Kinesigenic Dyskinesia (PKD), and the potential influence of the brain network stability gene PRRT2 on the structural connectome in PKD. Thirty‐five PKD patients with PRRT2 mutations (PKD‐M), 43 PKD patients without PRRT2 mutations (PKD‐N), and 40 demographically‐matched healthy control (HC) subjects underwent diffusion tensor imaging. Graph theory and network‐based statistic (NBS) approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…These results may relate to alterations of GM structure, for which there is some evidence in PKD: direct evidence from high‐resolution T1‐weighted MRI studies have identified morphometric/volumetric GM changes in presupplementary motor area, inferior frontal gyrus (H. F. Li et al, 2019) and thalamus (Kim et al, 2015); indirect evidence from secondary PKD reported that PKD was associated with various brain abnormalities for example, in thalamus (Camac, Greene, & Khandji, 1990), putamen (Merchut & Brumlik, 1986), right frontotemporal region (Gilroy, 1982), and globus pallidus (Micheli, Fernandez Pardal, Casas Parera, & Giannaula, 1986). Our morphological network findings are consistent with a structural brain network study using DTI, which showed “weaker small‐worldness” in PKD (L. Li et al, 2020). However, there was no significant change in functional global network properties in a study of drug‐naïve PKD patients using resting‐state functional MRI (Y. Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These results may relate to alterations of GM structure, for which there is some evidence in PKD: direct evidence from high‐resolution T1‐weighted MRI studies have identified morphometric/volumetric GM changes in presupplementary motor area, inferior frontal gyrus (H. F. Li et al, 2019) and thalamus (Kim et al, 2015); indirect evidence from secondary PKD reported that PKD was associated with various brain abnormalities for example, in thalamus (Camac, Greene, & Khandji, 1990), putamen (Merchut & Brumlik, 1986), right frontotemporal region (Gilroy, 1982), and globus pallidus (Micheli, Fernandez Pardal, Casas Parera, & Giannaula, 1986). Our morphological network findings are consistent with a structural brain network study using DTI, which showed “weaker small‐worldness” in PKD (L. Li et al, 2020). However, there was no significant change in functional global network properties in a study of drug‐naïve PKD patients using resting‐state functional MRI (Y. Zhang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Three studies have investigated structural abnormalities in patients with PKD using other techniques. Two of them used graph theory applied on structural covariance of GMV 35 and white matter properties 36 but did not include the cerebellum in the construction of the morphologic network used in the analyses. The remaining study investigated the basal ganglia and found a decrease in GMV and white matter abnormalities in the medial thalamus in patients with PKD.…”
Section: Discussionmentioning
confidence: 99%
“…39 Li et al investigated the topological characteristics of white matter structural networks and found decreased nodal characteristics in the left thalamus and left inferior frontal gyrus. 40 These studies further confirmed that the thalamo-cortical connectivity abnormality plays an important role in the pathophysiological mechanisms of PKD.…”
Section: Dti and Structural Mrimentioning
confidence: 59%
“…Long et al combined fMRI and DTI studies and found that the functional connectivity and structural connectivity between the ventrolateral/anterior thalamic nucleus and the motor cortex of PKD patients were significantly enhanced 39 . Li et al investigated the topological characteristics of white matter structural networks and found decreased nodal characteristics in the left thalamus and left inferior frontal gyrus 40 . These studies further confirmed that the thalamo‐cortical connectivity abnormality plays an important role in the pathophysiological mechanisms of PKD.…”
Section: Neuroimaging Studies Of Pkdmentioning
confidence: 95%